2024
DOI: 10.1101/2024.03.23.586403
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Analysis of Protein Cysteine Acylation Using a Modified Suspension Trap (Acyl-Trap)

Michael T Forrester,
Jacob R Egol,
Aleksandra Tata
et al.

Abstract: Protein cysteine thiols undergo reversibleS-acylation via a thioester linkage in vivo.S-palmitoylation, modification by C16:0 fatty acid, is a commonS-acylation that mediates protein-membrane and protein-protein interactions critical to an array of biological processes, from homeostatic lung surfactant function to cellular transformation. The most widely usedS-acylation assays, including acyl-biotin exchange (ABE) and acyl resin-assisted capture (Acyl-RAC), utilize blocking of free Cys thiols, hydroxylamine-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…Due to the presence of a reactive thiol, cysteine is an amino acid that plays a key role in enzyme catalysis. Beyond catalysis, cysteine side chains are frequently covalently modified, with succination 22 , nitrosylation 23 , and palmitoylation 24,25 being some of the more common cysteine-based PTMs. Reactive oxygen species (ROS) are also mediated through post-translational modification of the cysteine side chain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the presence of a reactive thiol, cysteine is an amino acid that plays a key role in enzyme catalysis. Beyond catalysis, cysteine side chains are frequently covalently modified, with succination 22 , nitrosylation 23 , and palmitoylation 24,25 being some of the more common cysteine-based PTMs. Reactive oxygen species (ROS) are also mediated through post-translational modification of the cysteine side chain.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have repeatedly identified many sites of modification that are not positively identified as being palmitoylated by MS. Short-chain acyl modifications to cysteine were not known in the literature and not searched for and hence could not be observed even if present. 24,33,34 The presence of thioester bound acyl-cysteine sites that did not map to known sites of palmitoylation hinted at the existence of short-chain cysteine acylomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation